2023
DOI: 10.1038/s41598-023-34956-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between smoking and obstructive sleep apnea based on the STOP-Bang index

Abstract: Smoking is a risk factor for respiratory diseases, and it worsens sleep quality due to nicotine stimulation and sudden nicotine withdrawal during sleep. This can increase the severity of OSA through alterations upper airway inflammation and neuromuscular function, arousal mechanisms, and sleep architecture. Therefore, it may lead to sleep-disrupted breathing, particularly obstructive sleep apnea (OSA). Herein, this study aims to research the association between smoking and OSA through the STOP-Bang index. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 61 publications
1
5
0
1
Order By: Relevance
“…This large, nationally representative cross-sectional study found significant associations between smoking and various sleep outcomes, including insufficient sleep duration, sleep problems, snoring, and snorting or stop breathing during sleep. Doseresponse analyses revealed that the odds of these sleep outcomes increased with higher smoking frequency, consistent with previous studies that smokers would have an elevated prevalence of sleeping disorders (Cohrs et al, 2014;Jang et al, 2023;Liao et al, 2019). However, our study provides more solid evidence due to the large sample size and examination of dose-response relationships.…”
Section: Discussionsupporting
confidence: 90%
“…This large, nationally representative cross-sectional study found significant associations between smoking and various sleep outcomes, including insufficient sleep duration, sleep problems, snoring, and snorting or stop breathing during sleep. Doseresponse analyses revealed that the odds of these sleep outcomes increased with higher smoking frequency, consistent with previous studies that smokers would have an elevated prevalence of sleeping disorders (Cohrs et al, 2014;Jang et al, 2023;Liao et al, 2019). However, our study provides more solid evidence due to the large sample size and examination of dose-response relationships.…”
Section: Discussionsupporting
confidence: 90%
“…there are studies that support the possible interactions between smoking, sleep quality, and respiratory problems. For example, a study by Jang et al found that smoking was associated with an increased risk of obstructive sleep apnea (OSA), a common respiratory disorder that can lead to poor sleep quality (30).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the association between hypertension and OSA has been identi ed to be bidirectional, with elevated BP signi cantly increasing the incidence of OSA, and OSA also increasing the risk of hypertension, especially resistant hypertension [31]. While studies evaluating the relationship between smoking and OSA have yielded inconsistent results, a recent study conducted by Jang et al among 3,442 participants of the Korea National Health and Nutrition Examination Survey found a positive dose-dependent relationship between smoking and the risk of OSA, with smoking cessation helping to properly manage sleep quality [32]. As a comprehensive assessment of lifestyle habits, the LS7 metrics may be a superior risk assessment tool for predicting the risk of OSA.…”
Section: Discussionmentioning
confidence: 99%